Cameron’s Tories : Talking Conservative, Acting Radical - Harry Cheesman (Revue LISA)
The UK’s first year of Con-Lib coalition government has seen radicalism in policy which even Mrs Thatcher would have baulked at, with policies on health and education going to the very root of the relationship of state and individual, and a determined Euroscepticism which seems to go further than that of the Thatcher years. The “Iron Lady” was notoriously cautious in her treatment of the NHS, whilst the introduction of university fees was never an option seriously considered during her administration ; the Conservatives under Cameron have happily trebled them. What does this tell us about Cameroon Conservatism ? It is the purpose of this paper to show that, whilst in a wide range of policy areas Mr Cameron’s Conservatives have clearly taken inspiration from “mother”, and have in fact demonstrated a reformist zeal which throws their heroine’s caution into surprising relief, that they have reversed one of her key teachings ; instead of following the doctrine of “talk radical, act conservative”, Cameron’s Tories are more likely to “talk conservative, act radical”.